Recent trends in formal and analytic solutions of diff. equations : Virtual Conference Formal and Analytic Solutions of Diff. Equations, June 28-July 2, 2021, University of Alcalá, Alcalá de Henares, Spain - Filipuk, Galina; Lastra, Alberto; Michalik, Sławomir; Virtual Conference Formal and Analytic Solutions of Diff. Equations (Contemporary mathematics, 2023)
This volume contains the proceedings of the conference on Formal and Analytic Solutions of Diff. Equations, held from June 28-July 2, 2021, and hosted by University of Alcala, Alcala de Henares, Spain. The manuscripts cover recent advances in the study of formal and analytic solutions of different kinds of equations such as ordinary differential equations, difference equations, $q$-difference equations, partial differential equations, moment differential equations, etc. Also discussed are related topics such as summability of formal solutions and the asymptotic study of their solutions. The volume is intended not only for researchers in this field of knowledge but also for students who aim to acquire new techniques and learn recent results.